Nonunidirectional energy exchange upon the steady-state two-wave interaction in a cubic gyrotropic photorefractive crystal in a dc electric field; Квантовая электроника; Т. 31, № 11 - Litvinov R. V. Rudolf Viktorovich (2001, 2001)
Заглавие с экрана